Piano pleasure course / Sarah Nurhannah Mohd Aziz and Syazali Effendi A Wahab - Mohd Aziz, Sarah Nurhannah; A Wahab, Syazali Effendi (Academy of Language Studies, 2023)
Piano Pleasure Course is an online platform that provides lessons to the public in creative ways. The content was created to capture the attention of those who are eager to invest their time in learning how to play piano. Unlike physical classes, the online teaching method's main purpose is to give lessons that are allowed to be referred to in the audience’s free time and no cost is charged for consultation and learning. The enthusiasm of students in many offline courses fades away over time. Christians (2022) found that online courses have shown a 25%–60% rise in student retention rates due to the development of interesting multimedia material, greater flexibility in how people consume the curriculum, and fewer instances of classes interfering with other obligations. The outcome of this project will allow me to expand my skills and conduct my own private tutoring lessons where the author will be a personal teacher to any student’s doorstep, this service can also expand up to the idea of launching a music academy. After an appropriate amount of research through surveys and online references it has come to my attention that there are many people regardless of gender and age that have great intentions in taking piano lessons however, they are faced with various restrictions including time and finances. Therefore, the author believes this online learning platform would contribute to ensuring the intended audience to gain satisfaction in pursuing piano.